2002
DOI: 10.1046/j.1365-2133.2002.04900.x
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic camouflage advice improves quality of life

Abstract: When assessed at 1 month, attendance at a cosmetic camouflage clinic appears to improve QoL significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
88
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 10 publications
4
88
2
1
Order By: Relevance
“…Other studies, evaluating patients with different disfiguring dermatoses, found that quality of life improvement was, at least partly, determined by the underlying condition [10, 17]. This is the first study on a larger sample of exclusively vitiligo patients.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Other studies, evaluating patients with different disfiguring dermatoses, found that quality of life improvement was, at least partly, determined by the underlying condition [10, 17]. This is the first study on a larger sample of exclusively vitiligo patients.…”
Section: Discussionmentioning
confidence: 80%
“…These two items were more affected in women with potentially disfiguring skin diseases but also in a vitiligo sample with equally distributed sexes [3, 17, 22]. Further analysis of the DLQI items in this study shows that vitiligo impairs the patient’s functioning in social and leisure activities, especially when affected body parts are visible or outside home or the family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with acne who do not wish to undergo surgical or physical interventions (i.e. laser treatments, injection, and plastic surgery), simple cosmetic cover on the acne scars, oily skin, or discoloration can improve the reported QOL [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These prior treatment options include cosmetic tattooing, mediumdepth chemical peels, carbon dioxide resurfacing, dermabrasion, skin grafting, and cosmetic camouflage. [5][6][7][8] popigmentation is needed. A treatment that increases melanin production could theoretically correct hypopigmentation regardless of whether it is caused by hypomelanocytosis, hypomelanosis, or optical factors.…”
mentioning
confidence: 99%